2004
DOI: 10.1086/423794
|View full text |Cite
|
Sign up to set email alerts
|

On the Survival of Short‐Period Terrestrial Planets

Abstract: The currently feasible method of detecting Earth-mass planets is transit photometry, with detection probability decreasing with a planet's distance from the star. The existence or otherwise of short-period terrestrial planets will tell us much about the planet-formation process, and such planets are likely to be detected first, if they exist. Tidal forces are intense for short-period planets and result in decay of the orbit on a timescale that depends on properties of the star as long as the orbit is circular.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 38 publications
1
65
0
Order By: Relevance
“…That the existence of Jupiter and Saturn affects the formation of Earth and the rest of the inner solar system, particularly in the vicinity of the asteroid belt, is well established (Wetherill 1992;Lecar & Franklin 1997;Chambers & Cassen 2002;Levison & Agnor 2003;Mardling & Lin 2004). The distribution of extrasolar planetary masses is securely predicted to show a similar bimodality (e.g., Ida & Lin 2004), due to the rapid timescale on which runaway accretion of giant planet envelopes occurs (Pollack et al 1996), so a coupling between the observed properties of the giant and terrestrial planets in the same system is expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That the existence of Jupiter and Saturn affects the formation of Earth and the rest of the inner solar system, particularly in the vicinity of the asteroid belt, is well established (Wetherill 1992;Lecar & Franklin 1997;Chambers & Cassen 2002;Levison & Agnor 2003;Mardling & Lin 2004). The distribution of extrasolar planetary masses is securely predicted to show a similar bimodality (e.g., Ida & Lin 2004), due to the rapid timescale on which runaway accretion of giant planet envelopes occurs (Pollack et al 1996), so a coupling between the observed properties of the giant and terrestrial planets in the same system is expected.…”
Section: Discussionmentioning
confidence: 99%
“…This schedule probably precedes the final stages of terrestrial planet formation. Chambers & Cassen (2002), Levison & Agnor (2003), and Mardling & Lin (2004) have studied in detail the effect of the giant planet configuration and its evolution on the formation of terrestrial planets. If, conversely, eccentricity is the endpoint of gravitational scattering among several massive planets, then the dynamics involved in the scattering process will usually involve multiple rearrangements of the planets prior to stabilization (usually by ejection) and establishment of a ''final'' configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, there is little evolution if the orbit starts close to circular, but the presence of much larger planets in close proximity suggests that a finite eccentricity would be excited by secular perturbations anyway, resulting in tidal evolution (e.g. Mardling & Lin 2004). Thus, we need to consider the fact that the currently observed configuration could be the result of substantial tidal migration if we wish to infer something about the origin and evolution of this planetary system.…”
Section: Tidal Evolution In the Classical Secular Approximationmentioning
confidence: 99%
“…Tides raised by Neptune on its moons help to constrain the planet's quality factor to 10 3.95 < Q < 10 4.56 (Zhang & Hamilton 2008). For M dwarfs, Q dM is assumed to be of order 10 5 , whereas for rigid bodies like Earth 20 Q 500 (Ray et al 2001;Mardling & Lin 2004, and references therein). For BDs, however, Q is even more uncertain, thus we will handle it as a free parameter in our procedures.…”
Section: Tidal Modelsmentioning
confidence: 99%